2019
DOI: 10.1021/acsami.9b17236
|View full text |Cite
|
Sign up to set email alerts
|

Multiresponsive Supramolecular Luminescent Hydrogels Based on a Nucleoside/Lanthanide Complex

Abstract: Supramolecular luminescent hydrogels based on natural molecules have shown high potential for a variety of applications because of unique optical properties and biocompatibility, particularly serving as advanced biomaterials for bioimaging, biosensing, cell engineering, and so forth. A lanthanide complex-based system provides a promising way to prepare supramolecular luminescent hydrogels. Herein, we realize the creation of a luminescent hydrogel assembled from lanthanides and nucleosides. Nucleosides, the ess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 46 publications
1
24
0
Order By: Relevance
“…Photoluminescent lanthanide derived hydrogels have advantages over conventional materials since they can be engineered for sensing applications in analytical, environmental, biological and medical fields [30,31] . During the past decade, a significant number of hydrogels based on macromolecules and low molecular weight gelators have been designed for sensing biologically or environmentally important molecules through sensitized lanthanide luminescence [32–34] . In this section, the sensing applications of hydrogels by means of sensitized lanthanide photoluminescent (PL) signal will be discussed.…”
Section: Photoluminescent Hydrogels As Sensorsmentioning
confidence: 99%
“…Photoluminescent lanthanide derived hydrogels have advantages over conventional materials since they can be engineered for sensing applications in analytical, environmental, biological and medical fields [30,31] . During the past decade, a significant number of hydrogels based on macromolecules and low molecular weight gelators have been designed for sensing biologically or environmentally important molecules through sensitized lanthanide luminescence [32–34] . In this section, the sensing applications of hydrogels by means of sensitized lanthanide photoluminescent (PL) signal will be discussed.…”
Section: Photoluminescent Hydrogels As Sensorsmentioning
confidence: 99%
“…In addition to the thermal-activated non-radiative decay, many other factors may be activated or influenced by temperature, including the effective molecular conformation or configuration transformation of flexible systems, 61,62 the degree of inter-or intramolecular π-π stacking and metal-metal interactions existing in aggregates or clusters of Rh(I), Pt(II), Cu(I), Ag(I), and Au(I) complexes, 39,[63][64][65] the dynamic association or dissociation process of metal and lanthanide complexes, 66,67 phase transition, [68][69][70][71] the degree of inter-or intramolecular energy transfer of donor/acceptor systems, 72,73 as well as the thermal equilibrium of different excited states. 74,75 These mechanisms will be discussed in more detail in specific examples in the following chapters.…”
Section: Zhong-liang Gongmentioning
confidence: 99%
“…However, the emission intensity changes could also be caused by many other factors, such as the dynamic association/dissociation process or phase transition. 66,71 The shift of λ emi is another general readout during the studies of thermo-responsive materials, which could be a result of dynamic thermal-equilibrium of different excited states or the change of the energy/electron transfer efficiency. 76,77 The shift of λ emi often leads to the emission color changes of materials, allowing us to conveniently monitor the thermo-responsive process.…”
Section: Zhong-liang Gongmentioning
confidence: 99%
“…Ma research group of Tianjin University [45] reported a fluorescent hydrogel composed of lanthanide and nucleoside. Here, nucleosides, the main component of nucleic acids, act as ligands and successfully chelate with lanthanide elements to form complexes in water.…”
Section: Multiresponse Supramolecular Luminescent Hydrogelmentioning
confidence: 99%